An Analysis Of Taqwa In The Holy Quran: Surah Al-Baqarah - Harison Mohd. Sidek; Sulaiman Ismail; Noor Saazai Mat Said; Mohd Aizuddin Abd Aziz; Suraini Mat Ali; Fariza Puteh Behak; Hazleena Baharun; Sulhah Ramli; Noor Azizi Ismail (OCERINT International Organization Center of Academic Research, 2024)
Indexed by WOS